Hydrocode simulations of the largest crater on asteroid Lutetia - Cremonese, G.; Martellato, E.; Marzari, F.; Kührt, E.; Scholten, F.; Preusker, Frank; Wünnemann, K.; Borin, P.; Massironi, M.; Simoni, E.; Ip, W-H.; OSIRIS, team (Planetary and Space Science, 2012)
The flyby of the Main Belt asteroid Lutetia by the Rosetta spacecraft allows the camera OSIRIS to obtain very good images of about half of the body at the maximum resolution of 60 m per pixel. From the images and radio-science experiment, a density of about (3.4±0.3) g/cm3 has been inferred for the asteroid. Many impact craters have been observed on the surface of Lutetia and the largest, named Massilia, has a diameter of about 55 km. Relative to the size of Lutetia (the longest axis is approximately 126 km) the crater represents one of the dominating features on its surface. Whether or not the impact that formed Massilia affected the entire asteroid can be only evaluated via numerical modeling, with hydrocodes, of the impact process. The results of a suite of iSALE simulations are compared with the crater profile derived from the Digital Terrain Model of the observed surface. The best match to the DTM of the crater with hydrocode simulations has allowed to determine a value of 7.5 km for the impactor diameter, which suggests a primordial origin of Lutetia due to the low probability of such an impact event. A second interesting impact structure has been identified nearby Massilia within the North Pole Crater Cluster. The crater has a diameter of 24 km and it lies over a larger crater of the North Pole Crater Cluster. This is strongly suggestive of a very young structure on Lutetia. The numerical simulations of this feature constrain the impactor to be 3.8 km in diameter, assuming the same material properties for target and impactor as in the model of the formation of Massilia.